Calculation of Visible Spectral Indices from UAV-Based Data: Small Water Bodies Monitoring - Čermáková, Ivana; Komárková, Jitka; Sedlák, Pavel (IEEE (Institute of Electrical and Electronics Engineers), 2019)
The paper describes utilization of an unmanned aerial vehicle (UAV) for detection of changes of small water areas and surrounding land cover. UAV is used as a cheap and on-demand available solution for remote data sensing. Its utilization is highly limited by legal regulations and weather conditions. The paper is focused on a monitoring of a small water body by means of vegetation spectral indices, which are calculated only from the visible part of the electromagnetic spectrum. The Normalized Excess Green Index (NExG), Normalized Green-Red Difference Index (NGRDI), Red-Green-Blue Vegetation Index (RGBVI), Green Leaf Index (GLI), Visible Atmospherically Resistant Index (VARI), and Vegetation Index of Excess Green (ExG) are used to classify the collected imagery and identify particular land cover types.
Výpočet viditelných spektrálních indexů z dat sebraných pomocí UAV: monitorování malých vodních ploch
Keywords: UAV; small water bodies; vegetation indices; visible indices; spectral indices; UAV; malé vodní plochy; vegetační indexy; viditelné indexy; spektrální indexy